Vaginal Protection by H(2)O(2)-Producing Lactobacilli - V. Sgibnev, Andrey (Jundishapur J Microbiol, 2015)
BACKGROUND: Peroxide-producing lactobacilli provide protection from infection for the female reproductive tract. However, in vitro studies demonstrated that H(2)O(2)-produced by Lactobacillus is not the cause of inhibition of pathogens. It is not exactly known how H(2)O(2)-producing lactobacilli are involved in the protection of the vaginal environment. OBJECTIVES: This study aimed to evaluate the importance of the interaction between H(2)O(2)-producing lactobacilli and their host for the resistance of the vaginal biotope. MATERIALS AND METHODS: In this study, we used vaginal lactobacilli (11 H(2)O(2)-roducing strains and 11 non-H(2)O(2)-producing strains). The influence of epithelial cells on the growth and antibacterial activity of lactobacilli were evaluated. The effects of lactobacilli on the antibacterial activity of the epithelial cells, muramidase and lactoferrin were also determined. RESULTS: Vaginal epithelial cells stimulated the growth and antibacterial activity of H(2)O(2)-producing lactobacilli in a greater extent than that of the non-H(2)O(2)-producing lactobacilli. Mainly, the H(2)O(2)-producing lactobacilli were capable of increasing the activity of the host antimicrobial peptides (muramidase and lactoferrin) as well as the antibacterial activity of the epithelial cells. CONCLUSIONS: The involvement of the peroxide-producing lactobacilli in the protection of vagina was due to their ability to effectively interact with the host. This is expressed on one side to stimulate the growth and antagonistic activity of lactobacilli and on the other side to increase the antibacterial activity of the host defense factors (muramidase, lactoferrin and metabolites of epithelial cells).